Iodoargentates from clusters to 1D chains and 2D layers induced by solvated lanthanide complex cations: syntheses, crystal structures, and photoluminescence properties. Issue 4 (5th January 2018) - Shen, Yali; Zhang, Limei; Sun, Peipei; Liu, Shuzhen; Jiang, Wenqing; Jia, Dingxian
Abstract : Lanthanide(iii ) iodoargentates [Ln(DMSO)8 ]4 Ag22 I34 ·2H2 O (Ln = La (1 ), Ce (2 )), [Ln(DMSO)8 ]Ag7 I10 (Ln = Eu (3 ), Tb (4 ), Dy (5 )), and [Yb(DMSO)7 ]Ag5 I8 (6 ) were synthesized by a diffusion method. Abstract : Organic hybrid lanthanide(iii ) iodoargentates [Ln(DMSO)8 ]4 Ag22 I34 ·2H2 O (Ln = La (1 ), Ce (2 )), [Ln(DMSO)8 ]Ag7 I10 (Ln = Eu (3 ), Tb (4 ), Dy (5 )), and [Yb(DMSO)7 ]Ag5 I8 (6 ) (DMSO = dimethyl sulphoxide) were synthesized by a diffusion method and structurally characterized. In1 and2, twenty AgI4 tetrahedra and two AgI3 triangles are connected via edge-sharing, forming the highly nuclear cluster [Ag22 I34 ] 12− . In3–5, the 2D [Ag7 I10 3− ] n layer is constructed from Ag10 I18 and Ag2 I5 secondary building units via edge-sharing. The parallel packing of the [Ag7 I10 3− ] n layers generates channels with cross-sectional dimensions of 5.5 × 18.2 Å 2, in which the [Ln(DMSO)8 ] 3+ counterions are trapped. In6, three AgI4 and two AgI3 units are joined via corner- or edge-sharing to form the asymmetric structural unit Ag5 I8 . The Ag5 I8 units are interconnected into a 1D [Ag5 I8 3− ] n chain via corner-sharing. The formation of [Ag22 I34 ] 12−, [Ag7 I10 3− ] n and [Ag5 I8 3− ] n anions indicates the different structure-directing effects of the Ln(iii ) ions across the lanthanide series. Compounds3 and4 display intense red and green luminescence at room temperature excited by 393 and 369 nm light, respectively.